Strategi Guru PAI Dalam Pengelolaan Kelas Inklusif Pada Siswa ADHD di SMP Asshiddiqiyah - Siti Rosita (Advances In Education Journal, 2025)
This study aims to describe the strategies employed by Islamic Religious Education (PAI) teachers in managing inclusive classrooms that include students with Attention Deficit Hyperactivity Disorder (ADHD) at SMP Asshiddiqiyah. The background of this research is based on the reality that PAI teachers face significant challenges in creating inclusive and adaptive learning environments, particularly because students with ADHD have specific characteristics such as difficulty maintaining attention, impulsive behavior, and a need for emotional-based approaches.This study uses a qualitative approach with a case study method. Data were collected through in-depth interviews with PAI teachers, guidance and counseling (BK) teachers, and the school principal, as well as through observation and documentation. Data analysis was conducted through data reduction, data display, and conclusion drawing.The findings indicate that the strategies implemented by PAI teachers include adaptive lesson planning, adjustment of teaching methods and learning media, and flexible evaluation for students with ADHD. Classroom management is carried out through classroom atmosphere arrangement, intensive supervision, and active involvement of regular students, although it is constrained by the absence of a special education companion teacher (GPK). The dominant characteristics of students with ADHD include high distractibility, impulsive behavior, and dependence on emotional approaches. In practice, PAI teachers collaborate with BK teachers and receive support from the school principal, although such support remains limited.This study concludes that the effectiveness of PAI teachers’ strategies largely depends on their understanding of students’ characteristics, their ability to adapt instructional practices, and collaborative support from the school environment